Anti-inflammatory effects of phosphatidylcholine - Treede, Irina (2015)
We recently showed that mucus from patients with ulcerative colitis, a chronic inflammatory disorder of the colon, is characterized by a low level of phosphatidylcholine (PC) while clinical studies reveal that therapeutic addition of PC using slow release